2006
DOI: 10.2164/jandrol.106.000539
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization and Possible Functional Role of PSP‐I/PSP‐II Heterodimer in Highly Extended Boar Spermatozoa

Abstract: PSP-I/PSP-II heterodimer is a major protein of boar seminal plasma which is able to preserve, in vitro, the viability, motility, and mitochondrial activity of highly extended boar spermatozoa for at least 5 hours. However, little is known about the binding pattern of the heterodimer to the sperm plasma membrane and its eventual relation with the maintenance of the sperm functionality. The present study investigated the effect of exposing highly extended boar spermatozoa (1 million/mL) to 1.5 mg/mL of PSP-I/ PS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 22 publications
4
38
0
Order By: Relevance
“…Caballero et al (2006) confirmed the protective effect role of fertility-associated PSP proteins by electron microscopic study and reported that these proteins were localized on the acrosomal and post-acrosomal regions of the sperm head and were distributed to other parts during incubation.…”
Section: Mitochondrial Membrane Potential Of Sperm Cellssupporting
confidence: 63%
“…Caballero et al (2006) confirmed the protective effect role of fertility-associated PSP proteins by electron microscopic study and reported that these proteins were localized on the acrosomal and post-acrosomal regions of the sperm head and were distributed to other parts during incubation.…”
Section: Mitochondrial Membrane Potential Of Sperm Cellssupporting
confidence: 63%
“…Furthermore, proteins from DRMs and non-DRMs are lost after capacitation and the acrosome reaction. These results are consistent with previous reports that describe the release of sperm membrane proteins during capacitation of bull [70], boar [71,72], rabbit [73] or ram [74] spermatozoa.…”
Section: Discussionsupporting
confidence: 93%
“…There are several proteins with sperm-coating and zinc-binding properties, which also have a positive impact on the parameters of the stored spermatozoa. The main boar seminal plasma zinc-binding spermadhesin -PSPI/PSPII, exerted positive effects on highly-diluted boar spermatozoa viability, motility and mitochondrial activity (7,10). ZnBPs of boar seminal plasma allowed preservation of a higher percentage of cells exhibiting linear motility and a higher percentage of intact acrosomes when stored at 4ºC (19).…”
Section: Discussionmentioning
confidence: 99%